Prevalence of ovine lung worm at Jucavm open air veterinary clinic, Southwest Ethiopia - Gudata, Daba (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
A cross sectional study was conducted in Jimma university veterinary clinic, Ethiopia from April 2018 to May 2018. The objectives of study were to estimate the prevalence of lungworm infection and associated risk factors in sheep. Coproscopic examination was done by using a modified Baermann technique. Fecal samples were collected from randomly selected sheep of systematically chosen households. The study animals were composed of different breeds, age groups, sexes, management systems, and subjected to different health care conditions. Out of 384 sheep examined, 69 (17.9%) were found to be positive for one or more species of lungworm parasites. Dictyocaulus filaria (6.8%) was the predominant species of parasite identified followed by Muellerius capillaries (4.7%) Protostrongylus rufescens (2.6%) and mixed infection of D. filaria and M. capillaries (3.9%). There was statistically significant difference in prevalence of lungworm parasite (P<0.05)among the risk factor like body conditions of animals. Animals with young age, not dewormed, and managed under extensive production system were more infected with the parasites. On the other hand, the prevalence of the parasites among management, age groups, deworming history and sexes showed no statistically significant difference (P>0.05). Despite the smaller prevalence observed in this study, ovine lungworm is still a constraint to sheep in the area in different season of the year, and therefore, vigorous controlling strategy should be implemented to reduce the prevalence of infection.